2019
DOI: 10.33215/sjom.v2i3.109
|View full text |Cite
|
Sign up to set email alerts
|

Mediating Effect of Intellectual Capital on Corporate Governance and Performance of Conglomerates in Nigeria

Abstract: Purpose: The nature of diversification in the form of conglomerates is the research theme for this study. Thus, CG’s functions on FP on conglomerates firms of Nigerian economy was studied while applying IC as the mediating variable.  Design/Methodology: This research depends on archival data collected from the NSE. Firms have been chosen based on the convenient sampling method and an important parameter for judgment is Conglomerated firms. In order to get genuine results, ten years of financial data have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 27 publications
1
1
0
Order By: Relevance
“…Makki & Lodhi (2014), Nkundabanyanga (2016) and Bhattacharjee et al (2017) argue that board composition has a positive influence on company financial performance, as well as IC as a mediator. Bala et al (2019) confirm that board size and the independence of board members affect financial performance, with a mediating effect of IC. Iqbal & Zaib (2017) showed that in the banking sector, corporate governance reflected through the certain characteristics of the board has a significant positive impact on IC, and vice versa, i.e.…”
Section: Intellectual Capital Board Structure and Bank Performancesupporting
confidence: 53%
“…Makki & Lodhi (2014), Nkundabanyanga (2016) and Bhattacharjee et al (2017) argue that board composition has a positive influence on company financial performance, as well as IC as a mediator. Bala et al (2019) confirm that board size and the independence of board members affect financial performance, with a mediating effect of IC. Iqbal & Zaib (2017) showed that in the banking sector, corporate governance reflected through the certain characteristics of the board has a significant positive impact on IC, and vice versa, i.e.…”
Section: Intellectual Capital Board Structure and Bank Performancesupporting
confidence: 53%
“…In order to manage and make wise investments in IC, a large board is therefore useless [38]. Some other studies, such as the study of Asare et al [23], Bala et al [30], Ho and Williams [87,221], and Saruchi et al [181], show that the IC of banks does not depend on board size.…”
Section: Board Sizementioning
confidence: 99%
“…There are various variables used by different authors as control variables when studying the effect of corporate governance on intellectual capital. Three control factors have been employed to limit the effect of these factors on the intellectual capital of firms (size, leverage, and age) [14,29,30,51,118,137,202]. The control variables of the study are summarized in Table 2.…”
Section: Control Variablesmentioning
confidence: 99%
See 1 more Smart Citation
“…ROA reflects the effectiveness of utilising available assets in creating profits. The ratio of operating profits to total assets is used to calculate it (Chen et al, 2005;Pal & Soriya, 2012;Bala, Raja, & Dandgo, 2019). ROE represents the return generated on common stocks of shareholders, and it is recognised as an important financial indicator for owners of the firm (Chen et al, 2005;Pal & Soriya, 2012;Kamath, 2015).…”
Section: Regression Modelmentioning
confidence: 99%